What are the effects of ethnicity on English pop music artists in Singapore? - Chua, Jonathan Jian Xin (2015)
Up till late modernity, pop music has still been dominant for the mass media by capturing a majority of the youths and creating pop culture through the medium of music, which creates patterns social identification and grouping. This paper examines whether these patterns are a result of ethnicity, and its implications on the artists themselves. This paper argues that Singaporean English Pop music artists are not seen as a homogenous group of individuals, but with different identities based on their ethnicity, with factors such as experiences, opinions, motivations and agency which determines their social position. Through the interviews of social actors that influence and understand the English Pop Music scene, this paper suggests that ethnicity as a factor for determining social position is primary; but there exists a negotiation between popular cultural influences and technoculture.